Cover Image, Volume 27, Issue 11. Issue 11 (23rd October 2017) - Hussain, Suleman; Egbenya, Daniel Lawer; Lai, Yi‐Chen; Dosa, Zita J.; Sørensen, Jakob B.; Anderson, Anne E.; Davanger, Svend
Abstract : Cover legend: This cover image, by Suleman Hussain et al., is based on the Research Article The calcium sensor synaptotagmin 1 is expressed and regulated in hippocampal postsynaptic spines, DOI:10.1002/hipo.22761 .